Benefits of lymphadenectomy for upper tract urothelial carcinoma only located in the lower ureter: a bicentre retrospective cohort study - Cui, Yupeng; Lu, Youyi; Wu, Jitao; Quan, Changyi (Frontiers in Oncology, 2023)
Background:Upper tract urothelial carcinoma (UTUC) is a rare and highly malignant urothelial tumor originating from the renal pelvis and ureter associated with poor prognosis. It has been established that 70% of ureteral tumors occur in the lower ureter. Radical nephroureterectomy (RNU) with ipsilateral bladder cuff excision is regarded as the standard treatment for UTUC. Current evidence supports the role of lymph node dissection (LND) in determining tumor staging, but no consensus has been reached on the potential survival benefits. The present study retrospectively analyzed cases of UTUC limited to the lower ureter to evaluate the survival benefits of LND during RNU. Methods:The present study retrospectively analyzed data from patients with UTUC limited to the lower ureter from two medical centers from 2000 to 2016 and assessed the survival outcomes, including recurrence-free survival (RFS) and cancer specific survival (CSS). During subgroup analysis, we stratified by pathological tumor (pT) stages and postoperative adjuvant chemotherapy (AC). Results:The study cohort included 297 patients separated into LND (n=111) and non-LND (n=186) groups.The two groups were comparable except for the pathological N stage. The LND group was associated with superior survival in terms of RFS (27.0% vs. 18.3%, p=0.044) and CSS (53.2 vs. 39.8 %, p = 0.031) compared to the non-LND group (n=186). In pT2-4 patients, the LND group was associated with better 3-year RFS (50.5% vs. 32.3%, p<0.05), 5-year RFS (29.7% vs. 12.0%, p<0.05), and overall RFS (18.7% vs. 6.0%, p<0.05) than the non-LND group. Besides, the LND group was associated with a significantly better 3-year CSS (68.1% vs. 49.6%, p= 0.003), 5-year CSS (51.6% vs. 30.8%, p<0.05) and overall CSS (45.1% vs. 24.1%, p<0.05). In patients that underwent AC, the LND group had better survival benefits in terms of RFS (29.4 vs. 16.7%, p=0.023) and CSS (52.9% vs. 40.5%, p=0.038) compared to the non-LND group. Conclusions: LND has survival benefits in patients with UTUC localized to the lower ureter, especially for≥pT2 stage UTUC and AC cohorts. Overall, the therapeutic effect of LND in UTUC cannot be replaced by AC.